A modular speed-drooped system for high reliability integrated modular motor drives - Galassini, Alessandro; Costabeber, Alessando; Gerada, C.; Buticchi, Giampaolo; Barater, Davide (IEEE, 2016)
Future transportation challenges include a considerable reduction in pollutant emissions at a time when significant increase in demand is predicted. One of the enabling solutions is the electrification of transport systems as this should lead to improved operability, fuel savings, emission reduction, and maintenance. While state-of-the-art technology has demonstrable benefits there needs to be considerable advancement to meet future transportation affordability and emission targets. Primarily, electrical drives need an improved power density, an increased reliability, and a reduced specific cost. For this reason, integrated modular motor drives (IMMDs) present an attractive solution. Modularity leads to redundancy and easier integration. This paper presents a novel speed-drooped control system applied to motors fed by modular paralleled converters. This control technique allows precise speed regulation and power sharing among different segments showing improved fault tolerance and reliability. The design procedure and the power sharing dynamic have been presented and analyzed by means of MATLAB/Simulink and validated in a 3-kW experimental rig, showing good agreement with the expected performances